Abdominal manifestations in childhood-onset systemic lupus erythematosus. Issue 2 (3rd July 2006) - Richer, O; Ulinski, T; Lemelle, I; Ranchin, B; Loirat, C; Piette, J C; Pillet, P; Quartier, P; Salomon, R; Bader-Meunier, B
Abstract : Background: Childhood-onset lupus erythematosus is a rare disorder of unknown origin. Objectives: To describe the frequency of gastrointestinal manifestations at presentation of systemic lupus erythematosus SLE and at follow-up, and discuss the specific causes of these manifestations. Methods: Medical records of 201 patients with childhood-onset SLE followed up in French paediatric nephrological, haematological and rheumatological centres were reviewed and abstracted for gastrointestinal manifestations. Results: Gastrointestinal involvement was recorded in 39 (19%) children. The median (range) age at the time of initial gastrointestinal manifestations was 11.3 (4.5–16) years. Gastrointestinal symptoms were present at or occurred within 1 month after diagnosis in 32% patients. Abdominal pain was the most frequent symptom, present in 34 (87%) patients. It was mostly related to lupus involvement, especially ascites (n = 14) and pancreatitis (n = 12), more rarely to treatment-induced events (n = 1) or infection (n = 1) and never to events unrelated to SLE. Three children with surgical abdomen underwent a laparotomy before SLE was diagnosed, with a final diagnosis of lupus peritonitis and lupus acalculous cholecystitis. C reactive protein values were <40 mg/l in all but two patients who had surgical abdomen. Abdominal ultrasonography and computed tomography scans were abnormal in 58% and 83% of the evaluated patients, respectively. Corticosteroids, associated with intravenous cyclophospamide in eight patients, led to complete remission of gastrointestinal involvement in 30 of 31 treated patients. Conclusion: Gastrointestinal involvement is common in children with SLE, and is mainly due to primary lupus involvement. Corticoidsteroid treatment should be promptly considered in children with lupus presenting with abdominal pain after infectious disease; side effects of treatment and intestinal perforation have been excluded.